Cross-Country Analysis of Competitiveness Towards Innovation Potential Assessment for Industrials - Shvindina, Hanna; Taraniuk, Leonid; Kotenko, Stanislav; Awujola, Abayomi; Taraniuk, Karina; Hongzhou, Qiu (Journal of Eastern European and Central Asian Research (JEECAR), 2022)
The global competitiveness report reveals cross-regional and cross-country disparities, and the innovation development of industrials shows how difficult it is to build and support competitiveness at a high level and increase innovation potential. The bibliometric analysis proves the diversity of the studies in the field and the increasing trend in paper production. The lack of understanding of the link between different levels of competitiveness and the need to monitor and forecast innovative development necessitated the cross-country benchmarking of industrials’ innovation potential. The offered methodology is a seven-stage algorithm of innovation potential assessment, based on an existing GCI methodology modified to reveal innovation development differences, and tendencies for particular industries. The ranking was performed for major industrial countries to reveal the gaps in innovative activities and develop catch-up strategies.